The Jarimatika Extracurricular Programme in Developing Early Childhood Numeracy Skills - Muarifah, Siti Lailatul; Muthohar, Sofa; Fatmawati, Nilal Muna (THUFULA, 2026)
Early numeracy skills are the fundamental foundation for young children to master more complex mathematical concepts in the future. However, classical learning methods are often considered less enjoyable and challenging for children, thereby hindering their interest and the development of their numeracy skills. This research aims: (1) To describe the planning and implementation process of the Jarimatika extracurricular program, (2) To analyze the impact of the program on the development of children's early numeracy skills, and (3) To identify the supporting and inhibiting factors in its implementation. The research method used is descriptive qualitative with a case study approach. Data collection techniques were carried out through participant observation, in-depth interviews with teachers, and documentation studies. The results show that the implementation of the Jarimatika extracurricular program, which includes the stages of introduction, habituation, and repetition through songs and games, was carried out systematically and enjoyably. This program proved effective in developing children's early numeracy skills, particularly in the aspects of understanding number concepts, addition, and subtraction operations. The children became more enthusiastic, confident, and skilled in solving simple arithmetic problemsThe conclusion of this research affirms that the Jarimatika extracurricular program can serve as a significant innovative method for creating enjoyable and meaningful numeracy learning, while simultaneously strengthening children's numeracy skills from an early age